Stigma and depression among obese infertile women: a cross-sectional study - Koç, Özlem; Karakoç, Hediye; Ersöğütçü, Filiz (Springer Science and Business Media Deutschland GmbH, 2024)
Background: Obesity causes infertility through various pathways, including disruption of ovarian follicular development, qualitative and quantitative development of the oocyte, fertilization, embryo development, and implantation. In traditional societies such as Türkiye, having children is a determinant of social status. Stigma is defined as a negative sense of social difference from others. Depression is a common health problem in infertile women due to the stressful nature of treatment procedures, fear of treatment failure, and the patient’s inability to become pregnant. In this cross-sectional study, the sample consisted of 161 infertile women from an infertility outpatient clinic of a university hospital in Eastern Turkey. Results: It was determined that depression scores had a strong positive correlation with stigma scores. In the multiple regression analysis performed to evaluate the effects of five independent variables determined to have an effect on depression scores, it was seen that the independent variables explained depression levels by 80%. Conclusion: The findings of this study suggest that stigma and depression are significant factors affecting the psychosocial and emotional well-being of obese women experiencing infertility. These results underscore the potential need for more comprehensive psychosocial support and assessment for women experiencing infertility related to obesity. Obese patients should be informed about the importance of pre-pregnancy weight reduction and should be encouraged to lose weight before the treatment to reduce the poor obstetrical outcomes due to obesity. Additionally, evidence-based guidelines should be prepared for assisted reproductive techniques for fertility treatment in obese infertile women. © The Author(s) 2024.
Keywords: Depression; Infertility; Obesity; Stigma